Effect of different nitrogen sources and time of application on corn grain yield - Vettorazzi, Jéssica [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Galindo, Fernando Shintate [UNESP]; Dupas, Elisângela [UNESP]; Yano, Élcio Hiroyoshi [UNESP]; Buzetti, Salatiér [UNESP] (Southern Cross Publishing, 2018)
Alternatives to reduce N losses in soil and increasing nutrient utilization efficiency are important because of the complex dynamics of nitrogen in the soil. In this context, the objective of this study was to evaluate the mechanized application of N doses, at different times (sowing or top-dressing) and forms (surface or incorporated) using urea to evaluate N leaf concentration, production components and corn grain yield. The study was conducted in Selvíria - MS, Brazil, in an Oxisol with clay texture in Brazilian Cerrado. The experimental design was a randomized complete block design with four replicates, arranged in a 6 x 2 x 2 factorial scheme: 6 doses of N (0, 50, 100, 150, 200, 250 kg ha-1), 2 application times (fully sowing or top-dressing) and 2 application forms in the soil (surface and incorporated). The evaluations were: N leaf concentration, stem diameter, plant height, height of pin insertion, spike length and diameter, number of rows per spike, grains per row, and grains per spike, 100 grains mass and corn grain yield. The N application in surface would be more beneficial due to the greater operational capacity. We recommended the application of 153 kg ha-1 of N in the soil without incorporation at sowing or top-dressing time in a clayey texture soil and with additional irrigation.
Keywords: Grain yield; Nitrogen fertilization; Productive components; Urea; Zea mays L